Small hyperattenuating adrenal nodules in patients with lung cancer: Differentiation of metastases from adenomas on biphasic contrast-enhanced computed tomography - Cao, Lixiu; Zhang, Libo; Xu, Wengui (Frontiers in Oncology, 2023)
Objective To evaluate the value of biphasic enhanced CT (CECT) in the differential diagnosis of metastasis and lipoid poor adenoma (LPA) in lung cancer patients with unilateral small hyperattenuating adrenal nodule. Materials and Methods This retrospective study included 241 lung cancer patients with unilateral small hyperattenuating adrenal nodule (metastases, 123; LPAs, 118). All patients underwent plain chest or abdominal CT scan and biphasic CECT scan, including arterial and venous phase. Qualitative and quantitative clinical and radiological characteristics of the two groups were compared using univariate analysis. An original diagnostic model was developed using multivariable logistic regression, and then according to odd ratio (OR) of the risk factors of metastases, a diagnostic scoring model was developed. The areas under the receiver operating characteristic curves (AUCs) of the two diagnostic model were compared by DeLong test. Results Compared with LAPs, metastases were older and showed more frequently irregular in shape and cystic degeneration/necrosis (all p<0.05). Enhancement ratio on venous (ERV) and arterial(ERA) phase of LAPs were noticeably higher than that of metastases while attenuation values on unenhanced phase (CTU) of LPAs was noticeably lower than that of metastases(all p<0.05). Compared to LAPs, the proportion of male and III/ IV clinical stage and small cell lung cancer(SCLL) were significantly higher for metastases(all p<0.05). As for peak enhancement phase, LPAs showed relatively faster wash-in and earlier wash-out enhancement pattern than metastases (p <0.001). Multivariate analysis revealed age≥59.5years (OR: 2.269; p=0.04), male(OR: 3.511; p=0.002), CTU≥27.5HU (OR: 6.968; p<0.001), cystic degeneration/necrosis (OR: 3.076; p=0.031), ERV≤1.44, (OR: 4.835; p <0.001), venous phase or equally enhanced(OR: 16.907; p <0.001 or OR: 14.036;p <0.001), and clinical stage II or III or IV(OR: 3.550; p =0.208 or OR: 17.535; p =0.002 or OR: 20.241; p =0.001) were hazard factors for diagnosis of metastases. AUCs of the original diagnostic model and the diagnostic scoring model for metastases were 0.919 and 0.914, respectively; There was no statistical significance of AUC between the two diagnostic model(p=0.644). Conclusions Biphasic CECT performed well diagnostic ability in differentiating metastases from LAPs. The diagnostic scoring model is easy to popularize due to simplicity and convenience.